Toll-Like Receptors in Hepatic Ischemia/Reperfusion and Transplantation - John Evankovich; Timothy Billiar; Allan Tsung (Gastroenterology Research and Practice)
The family of Toll-like receptors (TLRs) function as pattern-recognition receptors (PRRs) that respond to a myriad of highly conserved ligands. These substrates include pathogen-associated molecular patterns (PAMPs) for the recognition of invading pathogens, as well as damage-associated molecular patterns (DAMPs) for the recognition of endogenous tissue injury. While the functions of TLRs are diverse, they have received much attention for their roles in ischemia/reperfusion (I/R) injury of the liver and other organs. The TLRs play central roles in sensing tissue damage and activating the innate immune system following I/R. Engagement of TLRs by endogenous DAMPs activates proinflammatory signaling pathways leading to the production of cytokines, chemokines and further release of endogenous danger signals. This paper focuses on the most recent findings regarding TLR family members in hepatic I/R injury and transplantation.